Mapping greenhouse plastic wastes in the west region of Portugal - Nanna, M. (2019)
Plastic materials are used in many applications in agriculture, as greenhouse and tunnel covering films, direct coverings, shading and protective nets, irrigation pipes, fertilizers bags, pots and others. In Mediterranean countries, plastic film is the most common greenhouse covering material. Because of direct exposure to solar radiation and wind, greenhouse plastic covers need to be replaced every 6 to 45 months, depending on the material. The huge quantities of plastic waste produced need proper management in order to avoid environmental and economic impacts. The plastic waste is usually recycled by special companies that collect and treat this waste material. The aim of this study was to apply geographical information systems (GIS) and photointerpretation techniques to evaluate the amount of plastic waste produced in one of the most important regions of greenhouse production in Portugal, the west region, specifically the Torres Vedras municipality. The methodology has integrated the characterization of the type of plastic covering material and the cartography of the greenhouse land units. It used Land Use Map 2007, Bing Map images and administrative boundaries to determine the geographical position and the type of greenhouses. For each administrative unit, the frequency and total greenhouse area were calculated. Identification of the type of plastic material was made by photointerpretation and direct interviews at one company that sells material for greenhouses in Torres Vedras. The database created allowed us to determine the amount of plastic used as greenhouse cover materials and to identify the needs for recycling in this area. The geodatabase produced is the first step to monitor plastic waste production in time and space.